2016
DOI: 10.3928/01477447-20160509-01
|View full text |Cite
|
Sign up to set email alerts
|

Cancellous Screws Are Biomechanically Superior to Cortical Screws in Metaphyseal Bone

Abstract: Cancellous screws are designed to optimize fixation in metaphyseal bone environments; however, certain clinical situations may require the substitution of cortical screws for use in cancellous bone, such as anatomic constraints, fragment size, or available instrumentation. This study compares the biomechanical properties of commercially available cortical and cancellous screw designs in a synthetic model representing various bone densities. Commercially available, fully threaded, 4.0-mm outer-diameter cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…These tools and instruments include needles, scalpels, a cutting saw, sharp retractors, bone hooks, osteotomes, drills, and screws. [1720] Although wearing double gloves is encouraged among orthopedic and trauma surgeons, it has been reported that up to 10.7% of the surgeons will have their inner gloves perforated. This compromises the surgeon–patient barrier exposing surgeons to direct blood contact.…”
Section: Discussionmentioning
confidence: 99%
“…These tools and instruments include needles, scalpels, a cutting saw, sharp retractors, bone hooks, osteotomes, drills, and screws. [1720] Although wearing double gloves is encouraged among orthopedic and trauma surgeons, it has been reported that up to 10.7% of the surgeons will have their inner gloves perforated. This compromises the surgeon–patient barrier exposing surgeons to direct blood contact.…”
Section: Discussionmentioning
confidence: 99%
“…A closely spaced, shallow thread design and a larger core-to-outer diameter ratio are typical of cortical screws. In contrast, cancellous screws have widely-spaced, deep threads and a smaller core-to-outer diameter ratio [23]. However, considering pedicle screw instrumentation in spinal surgery, most of the screw anchoring power is contributed from the cortical bone in the pedicle, whereas the contribution is much smaller for the cancellous bone in the vertebral body [24].…”
Section: Introductionmentioning
confidence: 99%
“…At present, axial pullout test is the standard method to test the fixation strength and stability of medical bone screws in biomechanical experiments on cadaveric and animal bone and in synthetic bone surrogates . This test assumes microfracture or bone resorption, caused by high axial pullout stress, to be the main reason for screw loosening.…”
mentioning
confidence: 99%